Analisis Hubungan Volume Kredit dan Non Performing Loan pada Tingkat Profitabilitas PT. Bank Rakyat Indonesia Cabang Makassar Ahmad Yani - Andi Muhammad Sofian Assuary Yahya; Baso Sardjan; Bakri Bakri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Analysys of the relationship the credit volume and non performing loans to the level of profitability in the PT. Bank Rakyat Indonesia (Persero), Tbk Branch Makassar Ahmad Yani. This study ains to determine credit volume with profitability and determine of non performing loans to profitability in PT. Bank Rakyat Indonesia (Persero), Tbk Branch Makassar Ahmad Yani studied during the last 4 years 2020-2023. Methods of analysis used in this study is desrkriktif analysis method, statistical analysis of correlation and determination by using primery data in PT. Bank Rakyat Indonesia (Persero), Tbk Branch Makassar Ahmad Yani. Based on the result obtained it can be seen that the increase in loan volume tends to increase profitability at the PT. Bank Rakyat Indonesia (Persero), Tbk Branch Makassar A. Yani, as well when the level of loan volume declined tends to declined profitability. While non performing loans and the level of profitability has a negative relationship. That is when the non performing loans has increased the level of profitability is low. Vice versa, when the non performing loans decreased, the level of profitability increase.